2018
DOI: 10.15446/rsap.v20n3.54315
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and demographic determinants of dengue incidence in Brazil

Abstract: Objetivo Analizar la distribución espacial de los casos de dengue dentro de un área urbana en el estado de Sao Paulo, sudeste de Brasil.Métodos Basados en una metodología creada por los autores, se organizaron los datos del censo brasileño de 2010 en una malla regular de 250x250 metros cada célula. Esta célula fue la unidad de análisis. En seguida, fueran gecodificadas todas las 1 688 residencias de los casos de dengue registrados en 2013 en la ciudad de Caraguatatuba para calcular la tasa de incidencia por cé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
(15 reference statements)
6
16
0
11
Order By: Relevance
“…Regarding Strategic Points, we found that the addition of one SP in an area tended to increase the dengue incidence rate by 3%, a result consistent with previous findings [26,27]. Although there are clear guidelines on how to monitor SPs, including mandatory inspection visits every fifteen days [24], limited financial resources, skilled professionals or even violence in an area can affect the regularity of these visits [26,54].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding Strategic Points, we found that the addition of one SP in an area tended to increase the dengue incidence rate by 3%, a result consistent with previous findings [26,27]. Although there are clear guidelines on how to monitor SPs, including mandatory inspection visits every fifteen days [24], limited financial resources, skilled professionals or even violence in an area can affect the regularity of these visits [26,54].…”
Section: Discussionsupporting
confidence: 87%
“…We also gathered data on Strategic Points (SPs), comprising locations such as junkyards, tire repair shops, deposits of recyclable materials, etc. They are essential for understanding dengue occurrence as these areas present huge potential to accumulate Aedes breeding sites [24,26,27]. Examples are shown in Fig 2.…”
Section: Methodsmentioning
confidence: 99%
“…The WHO is also highlighting the importance of an integrated strategy to improve the outcomes of healthcare systems in infectious disease control [6,55]. This is especially relevant in a disease such as dengue, whose dissemination patterns are influenced by numerous, multisectoral aspects [21]. Systemic approaches are also important for Health Geography, as the understanding of diseases' spatial distribution requires synergy between different domains of surveillance, environmental and public health [8].…”
Section: Discussionmentioning
confidence: 99%
“…This requires considering numerous multisectoral aspects, as many environmental and socioeconomic factors have been linked to the breeding of A. Aegypti. These can be related to the climate and man-made urban environments, such as the presence of stagnant water in houses and abandoned buildings, and inadequate water, sanitation systems, and waste management [21][22][23].…”
Section: Dengue Dengue Surveillance and Relevance In Global Public mentioning
confidence: 99%
“…A study in Brazil found that dengue is socially more likely to reach populations with low economic status (Johansen et al, 2018). In addition, the higher the level of education, the better the practice of implementing dengue prevention (Causa et al, 2019).…”
Section: Introductionmentioning
confidence: 99%